Evaluation of modulus of elasticity, nano-hardness and stiffness of TiCN coating deposited by PACVD - Shafiei, Seyed Mohammad Mahdi; Divandari, Mehdi; Boutorabi, Seyed Mohammad Ali (Technium: Romanian Journal of Applied Sciences and Technology, 2020)
Modulus of elasticity (E) and nano-hardness (H) of the TiCN coating deposited on AISI H12 steel by plasma assisted chemical vapor deposition (PACVD) have been measured from load–displacement curves, resulting from nano-indentation testing. Stiffness (S) of the coatings has been evaluated from the indentation method. A qualitative evaluation of interfacial strength between coating and substrate material was also performed by indentation method. Results indicated elastic modulus and stiffness of the coatings are in the range of 97.3–99.2 GPa and 67.8–70.6 MPam1/2 those are respectively lower and higher than those of the individual constituent ceramics.